Preoperative Indicators for 1-year Mortality in Elderly Individuals Following Hip Fracture Surgery Under A Multidisciplinary Team Co-Management Model: A Single-Centre Retrospective Observational Study - Yucheng Gao PhD; Shaoyang Zhou MD; Wang Gao MD; Yuanwei Zhang PhD; Liu Shi PhD; Tian Xie MD; Chuwei Tian MD; Hui Chen; Yunfeng Rui PhD (Geriatric Orthopaedic Surgery & Rehabilitation)
Background Elderly patients have an impaired functional state and multiple comorbidities, resulting in poor postoperative rehabilitation ability and high rates of disability and mortality. However, little evidence exists on mortality predictors for geriatric hip fractures within the context of the multidisciplinary team co-management model. This study aimed to investigate the incidence and explore preoperative indicators of 1-year mortality following hip fractures in the elderly under this model. Methods A total of 439 elderly patients (130 men and 309 women) surgically treated for hip fractures under the multidisciplinary team co-management model between January 2018 and June 2021were included. Data regarding demographics, health state-related variables, injury- and admission-related variables, and preoperative laboratory test results were collected from medical records. Univariate and multivariate logistic regression analyses were used to identify preoperative indicators for 1-year mortality. Results A total of 49 patients died within 1 year of hip fracture surgery between January 2018 and June 2021, with an accumulated mortality rate of 11.16%. In univariate analysis, 14 items were found to be significant. In the multivariable logistic regression model, age >85 years, body mass index <21.0 kg/m 2 , time from injury to admission >9.5 h, preoperative haemoglobin <117 g/L, serum albumin <33.9 g/L, lactate dehydrogenase >292 U/L, and blood urea nitrogen >8.5 mmol/L were the independent preoperative indicators for 1-year mortality after surgery in elderly patients with hip fracture under the multidisciplinary team co-management model. Conclusions This study establishes a novel set of preoperative predictors for 1-year mortality in geriatric hip fracture patients managed under an MDT model, distinct from previous investigations focusing on postoperative interventions. The identified indicators enable early risk stratification, facilitating timely preoperative optimization. These findings underscore the prognostic value of integrating clinical and biochemical markers before surgery, warranting validation in multicenter prospective studies. Further prospective studies should be conducted to elucidate these associations and assess the effectiveness of targeted measures.